Pengaruh Penambahan Air Kelapa dan Larutan Gula Putih terhadap Nilai Viskositas Nira Aren sebagai Identifikasi Kemurnian Nira Aren - Agussalim, Lalu; Pangga, Dwi; Ahzan, Sukainil (Jurnal Ilmiah IKIP Mataram, 2023)
This study aims to determine the effect of adding a mixture of coconut water and white sugar solution on the viscosity of palm juice. The method to measure viscosity in this study is to use a falling ball viscometer. In total there were 5 samples studied with storage times of 2 hours, 4 hours, 6 hours and 8 hours. Sample 1 is 100% pure palm juice. Sample 2 is 70% pure palm juice mixed with 30% coconut water. Sample 3 is 60% pure palm juice mixed with 40% coconut water. Sample 4 is 80% pure palm juice mixed with 20% white sugar solution. Sample 5 is 70% pure palm juice mixed with 30% white sugar solution. The values of each sample in storage periods of 2, 4, 6 and 8 hours, respectively, were samples 1 (1,474) (1.26) (1,632) (1.59) N.s/m3. Sample 2 (2,014) (1,844) (1,561) (1,738) N.s/m3. Sample 3 (1,148) (1,308) (1,717) (1,780) N.s/m3. Sample 4 (0.936) (0.943) (1.766) (1.632) N.s/m3. Sample 5 (0.798) (1.142) (1.255) (1.345) N.s/m3. From the results of the study, it can be concluded that the addition of a mixture of coconut water and white sugar solution has an effect on the viscosity of pure palm juice.